Framing negative eWOM via conjunctions: The language of customer communication in the luxury hotel sector on social media - Yau Ni Wan (Peoples' Friendship University of Russia (RUDN University), 2024)
In the digital age, social media has a significant impact on consumer perceptions. This business communication study examines the linguistic strategies used to express and repair negative electronic word of mouth (eWOM) in Hong Kong's luxury hotel sector. The data, which were collected from travel forums, consist of 17,344 words from online hotel reviews (11,647 words) and responses (5,697 words) made by the visitors and senior hotel management of 18 five-star hotels. Using systemic functional linguistics as a framework, this study analyses the logical relations that exist between expectant and concessive conjunctions, as well as the evaluative judgment resources present in an appraisal system. The analysis focuses on the poor service standards framed in the complaints and how the hotel management responds to such situations differently, particularly with respect to repairing customer expectations. This study also examines how loyal fans and frequent travellers present their customer identity when dealing with service-related issues. By developing an understanding of how luxury hotels manage customer complaints, repair customer relationships, and protect their brand reputation through dynamic interactions, this study can provide valuable communication insights for the hotel sector.